SEJARAH PEMBINAAN DAN PENGHIMPUNAN HADITS - Abdul Wahab Syakhrani; M. Ibnu Rabi (CV. Adiba Aisha Amira, 2023)
The period of the Prophet Muhammad SAW Hadith at this time is known as Asr al-Wahy wa al- Takwin, namely the time of revelation and the formation of Islamic society. Such a situation requires the seriousness and caution of the Companions as the first inheritors of Islamic teachings. The revelations revealed by Allah were explained by the Prophet through his words, deeds and taqrir. So that what is heard and witnessed by friends is a guideline for their practice and behavior. The second period of the history of the development of hadith is the time of the Rashidun Khulafa' (Abu Bakr, Umar ibn Khattab, Usman ibn Affan, and Ali ibn Abi Talib) which lasted around 11 H to 40 H. This period is called the period of the great companions. The definition of a friend according to the terms of hadith science agreed upon by the majority of hadith scholars, is a Muslim who has associated with or seen the Prophet and died in a state of being a Muslim. The involvement of the Prophet's companions in the process of receiving hadith is a necessity